Changes in the Contents Related to “Forest Science” Including Forest Civil Engineering in Forest and Forestry Education at Japanese Vocational High Schools - Inoue, Mariko; Oishi, Yasuhiko (Journal of the Japanese Forest Society, 2021)
Changings in educational goals and contents of subjects related to “forest civil engineering” at vocational high schools were analyzed using the “Education Ministry Guidelines” (1947-2017) and school textbooks. The subjects named “forest engineering” in 1947 were divided into three in 1970's: “felling and log hauling,” “forest machinery” and “sabo” (erosion control engineering). They were integrated into “forest civil engineering” in 1978. In the 1998 revision, the subjects were placed as two chapters under “forest science”. Until the 1990s, the educational purposes were to learn techniques and knowledge for restoration of devastated land and logging, including forest machinery and civil engineering. However, these were then changed into learning about forest conservation and its multiple utilizations. Educational contents were classified into four fields; 1) “general remarks,” including role and safety, 2) “timber production,” including operating plans, felling and bucking, yarding and log hauling, 3) “forest engineering,” including forest roads and forest machinery, and 4) “sabo,” including water and soil conservation and erosion control. The description in the textbooks has been changed by technology development. The contents of practical forestry works have been changed to forest conservation and utilization. The same trend was reported in “forest management” and “silviculture” in our previous studies. In conclusion, education has been affected by the change in educational goals from cultivation of specialized professional areas to specialized basic areas.